Visual health assessment of parous female southern right whales (Eubalaena australis) off the southern Cape coast, South Africa - Hörbst, Sandra (Department of Biological Sciences, 2020)
The long-term monitoring of the South African southern right whale population has revealed a decrease in sightings along the coast and an increase of calving intervals within the last few years, causing changes in the species´ demographics causing a decrease in annual population growth rate (6.5% y -1 ). Because reproductive success is linked to body condition, the purpose of this study was to conduct a visual health assessment based on overhead photographs from the annual aerial southern right whale surveys and detect potential links between visual health condition of parous females and the increased calving intervals. Additionally, it was aimed to find relationships between visual health of parous females and environmental indices of the Southern Ocean, representing food availability. To allow global comparison of the results, the method used for the visual health assessment was developed in collaboration with international southern right whale researchers from Australia and South Africa. The health indices were adapted from a visual health assessment method developed for northern right whales and include body condition, skin condition, the presence of cyamids around the blowholes and rake marks on the skin. The results showed that these health variables derived from overhead photographs were sufficient to detect visual health changes over time. Within the study period (2005 – 2017), there were two years in which whales had a significant decreased visual health (i.e. increased health score) than average; 2008 and 2014. No direct link between the observed health condition and calving intervals could be found, possibly due to the lack of data on calving intervals post-2014 as well asthe assessment of breeding females only (i.e. breeding females are in good enough conditions to reproduce). However, significant relationships were found between visual health and Southern Ocean productivity (p< 0.001) and climate indices (p < 0.05) with a 0-year lag. These results clearly indicate a link between southern right whale visual health condition and Southern Ocean food availability in one feeding ground, suggesting that this may be the primary feeding ground for parous females during pregnancy. Understanding the links between visual health, reproductive success and climate/food availability helps to understand changes in the population’s demographics and to predict the resilience of the species. Additionally, the standardization of the method allows for global comparison.